Long-term treatment with recombinant human pentraxin 2 protein in patients with idiopathic pulmonary fibrosis: an open-label extension study - Raghu, Ganesh; van den Blink, Bernt; Hamblin, Mark J; Brown, A Whitney; Golden, Jeffrey A.; Ho, Lawrence A; Wijsenbeek, Marlies S; Vasakova, Martina; Pesci, Alberto; Antin-Ozerkis, Danielle E; Meyer, Keith C; Kreuter, Michael; et al. (The lancet. Respiratory medicine, 2019)
Background - Patients with idiopathic pulmonary fibrosis (IPF) treated with PRM-151, a recombinant human pentraxin 2 protein, in a phase 2 double-blind, randomised controlled trial had significantly reduced decline in percentage of predicted forced vital capacity (FVC) and stabilised 6-min walking distance compared with placebo over a 28-week period. Here we report the 76-week results of an open-label extension study. - Methods - Patients who completed the 28-week double-blind period of the PRM-151-202 trial were eligible to participate in the open-label extension study. Patients previously enrolled in the PRM-151 group continued this treatment and those previously in the placebo group crossed over to PRM-151. All patients received PRM-151 in 28-week cycles with loading doses of 10 mg/kg by 60 min intravenous infusions on days 1, 3, and 5 in the first week of each cycle followed by one infusion of 10 mg/kg every 4 weeks. The primary objective of the open-label extension study was to assess the long-term safety and tolerability of PRM-151, which were assessed by analysing adverse events (AEs) up to week 76 in all patients who received at least one dose of PRM-151 during the open-label extension study. Exploratory efficacy analyses were done by assessing changes from baseline in percentage of predicted FVC and 6-min walking distance, with descriptive statistics to week 76 and with random-intercept mixed models to week 52. This study is registered with ClinicalTrials.gov, number NCT02550873, and with EudraCT, number 2014-004782-24. - Findings - Of 116 patients who completed the double-blind treatment period, 111 entered the open-label extension study (74 from the PRM-151 group and 37 from the placebo group). 84 (76%) of 111 patients received concomitant IPF therapy (pirfenidone n=55 or nintedanib n=29). AEs were consistent with long-term IPF sequelae. 31 (28%) patients had serious AEs. Those occurring in two or more patients were pneumonia (six [5%] of 111), IPF exacerbation (four [4%]), IPF progression (four [4%]), and chest pain (two [2%]). 21 (19%) patients had severe AEs, of which IPF exacerbation and IPF progression each occurred in two (2%) patients. Two (2%) patients experienced life-threatening AEs (one had pneumonia and one had small-cell lung cancer extensive stage). A persistent treatment effect was observed for PRM-151 in patients who continued treatment, with a decline in percentage of predicted FVC of −3·6% per year and in 6-min walking distance of −10·5 m per year at week 52. In patients who started PRM-151 during the open-label extension study, compared with the slopes for placebo, decline reduced for percentage of predicted FVC (from −8·7% per year in weeks 0-28 to −0·9% per year in weeks 28-52, p<0·0001) and 6-min walking distance (from −54·9 m per year to −3·5 m per year, p=0·0224). - Interpretation - Long-term treatment with PRM-151 was well tolerated and the effects on percentage of predicted FVC and 6-min walking distance were persistent on continuation and positive in patients who crossed over from placebo. These findings support further study of PRM-151 in larger populations of patients with IPF. - Funding - Promedior.